2010
DOI: 10.1111/j.1526-4637.2010.00975.x
|View full text |Cite
|
Sign up to set email alerts
|

Pain Symptoms Accompanying Chronic Poststernotomy Pain: A Pilot Study

Abstract: CPSP is an extensive pain syndrome. Sternal pain is frequently accompanied by pain of the head, neck, back, and upper extremities. Further research on the possible etiology is warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
22
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(25 citation statements)
references
References 25 publications
1
22
0
2
Order By: Relevance
“…Although most frequently affecting the thorax, chronic pain associated with cardiac surgery may also involve the upper and lower extremities, neck, and back, potentially explaining the difficulty in properly diagnosing chronic pain resulting from median sternotomy. 4,5,8 Thoracic pain following coronary artery bypass grafting (CABG) may be further divided into 3 different subcategories: (1) anterior chest wall pain on the left side, (2) midline scar pain, and (3) right-sided chest wall pain. Like the location of pain, descriptors are also varied, with some patients experiencing intermittent pain, whereas others describe constant pain.…”
Section: Diagnosismentioning
confidence: 99%
See 3 more Smart Citations
“…Although most frequently affecting the thorax, chronic pain associated with cardiac surgery may also involve the upper and lower extremities, neck, and back, potentially explaining the difficulty in properly diagnosing chronic pain resulting from median sternotomy. 4,5,8 Thoracic pain following coronary artery bypass grafting (CABG) may be further divided into 3 different subcategories: (1) anterior chest wall pain on the left side, (2) midline scar pain, and (3) right-sided chest wall pain. Like the location of pain, descriptors are also varied, with some patients experiencing intermittent pain, whereas others describe constant pain.…”
Section: Diagnosismentioning
confidence: 99%
“…2 Previous studies may have underestimated the incidence of chronic pain because of its variable presentation, accounting for some of the large variation in incidence between groups. 8 In addition, the diagnosis of chronic pain after sternotomy can be made only when reported. Given the considerable anxiety and fear surrounding cardiac surgery, patients may underreport pain as they are simply happy to have survived surgery and do not wish to complain about what they may consider comparatively trivial.…”
Section: Diagnosismentioning
confidence: 99%
See 2 more Smart Citations
“…The 2013 Canadian prospective Cardiac (CARD) pain study (n=1010) [11] reported more modestly varying CPSP prevalence rates of 40%, 22%, and 17% at 3, 6, and 12 months following surgery, respectively; pain was most commonly located along the sternal incision and saphenous vein harvesting sites. But other studies have reported 1-year CPSP prevalence rates as high as 39% [39] and 45% [40]. Rates of CPSP following vascular surgery are similar in range (25%), with moderate to severe pain typically presenting along the femoropopliteal bypass tunnel [42].…”
Section: Introductionmentioning
confidence: 99%